Co-assembled supramolecular hydrogels of cell adhesive peptide and alginate for rapid hemostasis and efficacious wound healing. Issue 42 (16th October 2019) - Zhai, Ziran; Xu, Keming; Mei, Leixia; Wu, Can; Liu, Jing; Liu, Ziqi; Wan, Lanxin; Zhong, Wenying
Abstract : Co-assembly of a cell adhesive peptide conjugate and alginate affords multifunctional composite hydrogels for rapid hemostasis and efficacious wound healing. Abstract : Injectable hydrogels are promising materials for applications in non-compressive wound management. Yet difficulties remain for the fabrication of mechanically stable hydrogel materials with inherent functionalities in both hemostatic control and wound healing without additional supplements of growth factors. Herein, we reported the co-assembly of a cell adhesive peptide conjugate (Pept-1) and alginate (ALG), to confer supramolecular hydrogels with excellent mechanical properties and high efficacy in both hemostatic control and wound healing requiring no additional growth factors. The co-assembling process of Pept-1 and ALG, which was mediated by electrostatic interactions and metal chelation, afforded a composite hydrogel with denser nanofibrillar structures and better mechanical strength when comparing to the Pept-1 gel alone. As-prepared Pept-1/ALG hydrogels exhibited excellent injectability and thixotropic properties, making them ideal materials for wound dressing. The composite hydrogel induced fast hemostasis when spiked with whole blood in vitro, and reduced the amount of bleeding to ∼18% of the untreated control in a liver puncture mouse model. Meanwhile, it promoted adhesion and migration of fibroblast NIH3T3 cells in vitro, and accelerated the rate of wound healing in a full-thickness skin defect model of mice. In addition, the Pept-1/ALG hydrogel showed excellent biocompatibility with no obvious hemolytic activity. In future, the strategy of utilizing co-assembled nanostructures composed of biofunctional peptides and polysaccharides could be further exploited to construct a broad range of nanocomposite materials for a variety of biomedical applications.